The use of a novel bone allograft wash process to generate a biocompatible, mechanically stable and osteoinductive biological scaffold for use in bone tissue engineering. (19th June 2014) - Smith, C. A.; Richardson, S. M.; Eagle, M. J.; Rooney, P.; Board, T.; Hoyland, J. A.
Abstract: Fresh‐frozen biological allograft remains the most effective substitute for the 'gold standard' autograft, sharing many of its osteogenic properties but, conversely, lacking viable osteogenic cells. Tissue engineering offers the opportunity to improve the osseointegration of this material through the addition of mesenchymal stem cells (MSCs). However, the presence of dead, immunogenic and potentially harmful bone marrow could hinder cell adhesion and differentiation, graft augmentation and incorporation, and wash procedures are therefore being utilized to remove the marrow, thereby improving the material's safety. To this end, we assessed the efficiency of a novel wash technique to produce a biocompatible, biological scaffold void of cellular material that was mechanically stable and had osteoinductive potential. The outcomes of our investigations demonstrated the efficient removal of marrow components (~99.6%), resulting in a biocompatible material with conserved biomechanical stability. Additionally, the scaffold was able to induce osteogenic differentiation of MSCs, with increases in osteogenic gene expression observed following extended culture. This study demonstrates the efficiency of the novel wash process and the potential of the resultant biological material to serve as a scaffold in bone allograft tissue engineering. © 2014 The Authors. Journal of Tissue Engineering and Regenerative Medicine published by John Wiley & Sons Ltd.